Study on the Support Effect of Energy-Absorbing Support Structure in the Coal Mine Roadway and the Synergic Effect with Wall Rock - Shuwen Wang; Shijie Su; Qian Zhao; Dong An; Yonghui Xiao; Hailiang Xu (Shock and Vibration)
This paper examines the effectiveness of energy absorption anti-impact support in protecting the coal mine roadway from rock burst and ensuring safe production. By establishing an ABAQUS numerical model of the support and wall rock, the mechanical behavior of the system under static and impact loads have been investigated. The analysis includes the deformation of the wall rock, plastic strain, plastic property, and damage range to evaluate the support effect and the synergistic effect with the wall rock. The findings indicate that compared to ordinary support, the energy absorption anti-impact support exhibits a 20.40% increase in maximum deformation, 4.74% increase in maximum stress, 66.67% decrease in maximum plastic strain, and 116.79% increase in maximum absorption energy. The wall rock also experiences a 2.91% increase in maximum deformation and 10.19% increase in maximum stress. These results suggest that energy absorption anti-impact support is effective in improving the anti-impact performance of the support and providing a certain level of protection to both the support and wall rock.